2021
DOI: 10.1101/2021.03.19.21253680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population homogeneity for the antibody response to COVID-19 BNT162b2 / Comirnaty vaccine is only reached after the second dose, across all adult age ranges

Abstract: While mRNA vaccines authorised for emergency use are administrated worldwide in an effort to contain the COVID19 crisis, little is known about the heterogeneity of the immune response they induce. Here, we report the first 6 weeks of a longitudinal study that quantifies the humoral immune response to BNT162b2 mRNA COVID-19 (Pfizer/BioNTech, Comirnaty) in 1245 health care providers, the Lx1000HCW-PZF cohort. We reveal a striking inter-individual variation 3 weeks after the 1st dose administration that only in p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
(32 reference statements)
9
6
0
Order By: Relevance
“…However, this association nearly vanished after dose 2 and lost statistical significance (ρ=-0.23, P=0.093). These findings align with recent articles, which found a gap in antibody levels of younger and older individuals after dose 1 ( Abu Jabal et al, 2021 , Müller et al, 2021 , Viana et al, 2021 ). A recently published prospective study by Lustig et al (2021) confirmed that older adults yield lower antibody levels after the first BNT162b2 dose, with the age groups converging after the second dose.…”
Section: Discussionsupporting
confidence: 92%
“…However, this association nearly vanished after dose 2 and lost statistical significance (ρ=-0.23, P=0.093). These findings align with recent articles, which found a gap in antibody levels of younger and older individuals after dose 1 ( Abu Jabal et al, 2021 , Müller et al, 2021 , Viana et al, 2021 ). A recently published prospective study by Lustig et al (2021) confirmed that older adults yield lower antibody levels after the first BNT162b2 dose, with the age groups converging after the second dose.…”
Section: Discussionsupporting
confidence: 92%
“…However, IgG levels after one vaccine dose were remarkably lower in hemodialysis patients when compared to age-matched controls below 70y. These results strengthen that the dynamics of anti-IgG responses across the vaccination schedule in hemodialyzed patients resembles those of elderly cohorts (8).…”
Section: Discussionsupporting
confidence: 78%
“…Our observations added to mounting evidence that age has a significant negative effect on antibody response to the BNT162b2 vaccine (5,6,8). However, IgG levels after one vaccine dose were remarkably lower in hemodialysis patients when compared to age-matched controls below 70y.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, this association nearly vanished after dose 2 and lost statistical significance (ρ=-0.23, P=0.093). These findings align with recent articles, which found a gap in antibody levels of younger and older individuals after the dose 1 (Müller et al, 2021, Viana et al, 2021).…”
Section: Discussionsupporting
confidence: 92%